Нові та маловідомі для території України види мікофільних грибів. II. Роди Acrodontium, Nodulisporium і Rhinotrichella - Акулов, О.Ю. (Український ботанічний журнал, 2011)
Работа содержит информацию о четырех видах микофильных гифомицетов: Acrodontium crateriforme (J.F.H.Beyma) de Hoog, A. hydnicola (Peck) de Hoog, Nodulisporium cecidiogenes Jørg.Koch и Rhinotrichella globulifera G.Arnaud ex de Hoog. Приводятся подробные описания и оригинальные иллюстрации этих видов, а также рассматриваются их экологические особенности. Acrodontium crateriforme до сих пор был известен по единичной находке, а остальные три впервые обнаружены в Украине. The paper contains information about four species of fungicolous hyphomycetes: Acrodontium crateriforme (J.F.H. Beyma) de Hoog, A. hydnicola (Peck) de Hoog, Nodulisporium cecidiogenes Jørg. Koch, and Rhinotrichella globulifera G. Arnaud ex de Hoog. Detailed descriptions, original illustrations and some ecological features of these species are provided. The last three species are recorded in Ukraine for the first time; A. crateriforme is known in the country from a single collection.